Application of Induced Pluripotent Stem Cell-Derived Models for Investigating microRNA Regulation in Developmental Processes - Chen, Hongyu; Zhang, Mimi; Zhang, Jingzhi; Chen, Yapei; Zuo, Yabo; Xie, Zhishen; Zhou, Guanqing; Chen, Shehong; Chen, Yaoyong (Frontiers in Genetics, 2022)
Abstract Advances in induced pluripotent stem cell (iPSC) techniques have opened up new perspectives in research on developmental biology. Compared with other sources of human cellular models, iPSCs present a great advantage in hosting the unique genotype background of donors without ethical concerns. A wide spectrum of cellular and organoid models can be generated from iPSCs under appropriate in vitro conditions. The pluripotency of iPSCs is orchestrated by external signalling and regulated at the epigenetic, transcriptional and posttranscriptional levels. Recent decades have witnessed the progress of studying tissue-specific expressions and functions of microRNAs (miRNAs) using iPSC-derived models. MiRNAs are a class of short non-coding RNAs with regulatory functions in various biological processes during development, including cell migration, proliferation and apoptosis. MiRNAs are key modulators of gene expression and promising candidates for biomarker in development; hence, research on the regulation of human development by miRNAs is expanding. In this review, we summarize the current progress in the application of iPSC-derived models to studies of the regulatory roles of miRNAs in developmental processes.